Awareness of Medan Area Students in Demanding Against the Law of Drug Abuse, the Prevention of Radicalism and Terrorism - Zaini Munawir S; Abdul Lawali Hasibuan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The progress of a nation can be seen from the level of legal awareness of its citizens. The higher the legal awareness of a country's population, the more orderly life of society and the state. Conversely, if the legal awareness of a country's population is low, what applies there is jungle law. Does the legal awareness of today's society need to be increased? Has it declined so much? What can we overcome in today's society related to legal awareness? In accordance with what has been stated above, that legal awareness is essentially awareness of the existence or occurrence of "unlawful" or "onrecht", let us see whether in today's society many things or events that are judged as "unlawful" or "onrecht". Indeed, the reality is that legal awareness is only being debated or crowded in the newspapers if legal awareness is declining or does not exist, if there are legal violations: drug abuse, radicalism and terrorism, murder, corruption, extortion, fraud , begal and so on. The level of legal awareness of students towards acts against the law uses four indicators, namely Legal Knowledge, Legal Understanding, Legal Attitudes and Legal Behavior.